Metastatic paranasal sinuses adenocarcinoma from breast carcinoma, a rare event: a case report - Khurayzi, Tawfiq; Alshahrani, Abdullah (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Metastases to the nose and paranasal sinuses usually respond poorly to treatment and have a poor prognosis. We present a 31 year old lady with rare metastatic paranasal sinuses lesion which is adenocarcinoma that metastasis from breast carcinoma. All of clinical presentation, radiological findings, histopathological and immunohistochemically markers examination reveal metastatic adenocarcinoma. This study presents rare metastasis in head and neck cancer especially from breast to paranasal sinuses.